HUMAN RESOURCE MANAGEMENT STRATEGY IN MSMEs TO FACE THE GLOBAL MARKET THROUGH INNOVATION AND DIGITAL TECHNOLOGY - Mariam, Siti; Idrus, Syech; Damayanti, Si Luh Putu; Bagiastra, I Ketut (Yayasan Education and Social Center, 2024)
This study examines the human resource management (HR) strategy in micro, small, and medium enterprises (MSMEs) as they confront the global market via innovation and digital technology. The research methodology employed is qualitative, utilizing an in-depth interview approach and case studies on numerous MSMEs that integrate digital technology into their HR management and product marketing processes. The study results show that MSMEs implementing digital technology in HR management have experienced increased operational efficiency, especially in employee data management, attendance, and payroll. However, the main challenges faced are the low digital skills of most employees and the high cost of implementing technology. In addition, the role of technology-savvy leadership is crucial in the success of the transition to a digital system. Using digital technology in marketing and product innovation also enables MSMEs to expand their market reach, including the global market. The results of this study show that the use of digital technology in human resources management and marketing is the most important factor for micro, small, and medium-sized enterprises (MSMEs) to improve their competitiveness and survive in the global market